Psychological Empowerment and Innovative Work Behavior: The Role of Transformational Leadership as Moderating Variable - Aristana, I Nengah; Wibawa, I Wayan Sucipta; Wisnawa, I Made Bayu (Jurnal Manajemen Bisnis, 2024)
Research aims: The objective of this research is to explore the effect of psychological empowerment on innovative work behavior with transformational leadership as a moderator.Design/Methodology/Approach: This research was designed using a quantitative approach where data was collected using questionnaires distributed to 190 employees of export SMEs in Bali. The gathered data was examined using Smart PLS 3.2.9 software.Research findings: The research found that psychological empowerment and its dimensions positively affected innovative work behavior. In addition, transformational leadership fully moderated the link between psychological empowerment and innovative work behavior. The limitation of the research indicated bias due to self-assessment reports. Meanwhile, the practical implications contribute to expanding understanding of the role of transformational leadership as a moderator. Thus, leaders have a reference in policy making.Theoretical Contribution/Originality: The theoretical contribution of this research contributes to the knowledge of on innovative work behavior by exploring psychological empowerment.Practitioners/Policy Implications: Practical implications contributed to expanding understanding of the moderating role of transformational leadership. Hence, leaders have a reference in policy making.Research Limitations/Implications: The sample used is still limited to the export SME sectors in Bali. This research uses a causality approach. Thus, the data reported is self-assessment.